Parent Connection: Enlisting Parents in Career Counselling - Sinacore, Ada L.; Healy, Patricia; Hassan, Sheila (Canadian Journal of Counselling and Psychotherapy, 2007)
Counsellors have long been aware of the influence of parents on the career development and decisions of their children, as has been documented in the literature. Although the potential impact of parental influence is recognized, attempts to enlist parents in positive ways often appear haphazard, rather than purposeful. Further, the literature shows parental aspirations to be gender specific, also varying according to cultural and socioeconomic factors. Herein, the authors offer numerous strategies to maximize the positive aspects of parental involvement in children's career development, by offering concrete steps to strengthen the parent-child partnership.